Safety and environmental friendliness measures at the service center (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
This scientific research work mainly addresses the issues of scientific substantiation of the impact of technical service and repair technological process indicators on the direct quality of rolling stock performance at road transport enterprises and ensuring the use of modern improved methods in these processes
Keywords: car, traffic safety, traffic, traffic signs, dangerous sit